Pengabdian masyarakat RUMBERIA (Rumah Belajar Ceria): RUMBERIA( Rumah Belajar Ceria) - Farhan, Muhammad; Lestari, Yulia; Sari, Suci Indah; Mujib, Abdul (LPPM Universitas Internasional Batam, 2023)
Rumberia activities (Rumah Belajar Ceria) are carried out 2 times in seminnggu on Saturdays and Sundays located in Nagori Purwosari, Pematang Bandar District, Simalungun Regency. This Rumberia activity ( Cheerful Learning House) is carried out with the aim of helping Nagori Purwosari's children to be good at reading and counting because the majority of Nagori Purwosari's children are lacking in reading and counting. In addition to teaching about reading and counting we also make a game where these children can more easily learn the lessons taught and make them not bored or tired in learning and this method is very effective in making Nagori children enthusiastic in learning. The service team also often uses a prop to make children more knowledgeable about to make children more knowledgeable about learning. The result of this devotion makes it easier for the children of Nagori Purwosari to understand in accordance with their imagination which makes it easier for them to defend